State policy towards the indigenous population in Poland after World War II (1945–1956) - Jankowiak, Stanisław (Balcanica Posnaniensia. Acta et studia, 2001)
The article is devoted to the policy of the Polish authorities toward the indigenous population living in the territories incorporated into Poland after the Second World War. The author analyzes the problem of determining the national status of inhabitants regarded as indigenous and the consequences of the verification and repolonization policies pursued toward them. The aim of the study is to present the mechanisms of state policy toward the indigenous population between 1945 and 1956 and to assess the effects of these measures. The research is based on the analysis of administrative records, materials from the Ministry of Public Administration, documents of the Polish Western Association, and sources relating to local authorities. The author argues that the principal instrument of state policy was nationality verification, intended to distinguish people of Polish origin from Germans designated for expulsion. The criteria adopted included, among others, knowledge of the Polish language, participation in Polish organizations, family ties, and declared national identification. In practice, however, the process frequently resulted in abuses and repression against the local population. Indigenous inhabitants were interned in labor camps, deprived of property, and treated as Germans despite their Polish origins. Government measures failed to achieve the full integration of this group. The Congress of Autochthons in 1946 revealed numerous problems and widespread disappointment with state policy. In subsequent years, nationality issues increasingly gave way to class-based criteria, while collectivization and repression directed against wealthier farmers further deepened the distrust of the indigenous population. The author concludes that state policy toward autochthons was inconsistent and burdened by numerous contradictions, which hindered the achievement of its intended integration goals.